Peningkatan Pengetahuan Tentang Hypnobreastfeeding untuk Peningkatan Produksi ASI pada Ibu Nifas di RS X - Aprillia, Rika; Rika Yunita Ernanda; Ida Sofiyanti; Wiwik Ardhiani (Universitas Ngudi Waluyo, 2025)
Exclusive breastfeeding is giving only breast milk without other foods and drinks to babies from birth to 6 months of age, except for drugs and vitamins (Word Health Organization, 2019). Breast milk is the best food for babies and has ideal nutritional content for baby growth and development. Exclusive breastfeeding from birth to six months of age without any additional food or drinks. Various ways are carried out by mothers so that the breastfeeding process can run smoothly and adequately in giving baby nitriation. One of the efforts that can be made is to hypnobreastfeeding. From the results of interviews that have been conducted at X Hospital on the 5 postpartum mothers on the first day said that their breast milk could not come out, the mother felt not confident that her breast milk would come out, especially in mothers who had just given birth for the first time. So we are interested in doing community service with the title